2023
DOI: 10.1088/1361-6528/ace057
|View full text |Cite
|
Sign up to set email alerts
|

Performance enhancement of HfO2-based resistive random-access memory devices using ZnO nanoparticles

Abstract: In this study, resistive random-access memory (ReRAM) devices with ZnO nanoparticles (NPs) are suggested to enhance performance and reduce variation in device switching parameters. The ZnO NPs are formed by annealing ZnO prepared via atomic layer deposition on HfO2, which is verified using transmission electron microscopy (TEM), X-ray diffraction pattern (XRD), and atomic force microscopy (AFM). The depth profile analysis of X-ray photoelectron spectroscopy (XPS) shows that oxygen diffuses from HfO2 to ZnO NPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The values of R DS were deduced as 9.6 kΩ, 2.7 MΩ, and 4.5 MΩ at V GS = 0 V for TFT-0, TFT-66, and TFT-100, respectively. The higher R DS of the TFTs confirmed that the introduction of oxygen atoms compensated for the oxygen vacancies in the ZnO channel layer, thus leading to a lower electron concentration and higher resistance [4,15,38].…”
Section: Resultsmentioning
confidence: 70%
“…The values of R DS were deduced as 9.6 kΩ, 2.7 MΩ, and 4.5 MΩ at V GS = 0 V for TFT-0, TFT-66, and TFT-100, respectively. The higher R DS of the TFTs confirmed that the introduction of oxygen atoms compensated for the oxygen vacancies in the ZnO channel layer, thus leading to a lower electron concentration and higher resistance [4,15,38].…”
Section: Resultsmentioning
confidence: 70%